Entre telas anda la palabra de Dios: la compleja iconografía de la Virgen con el Niño y san Juanito de Joan de Borgonya - Moreno Coll, Araceli (Eikón / Imago, 2025)
We aim to delve into the elaborate iconographic program of the painting the Virgin with the Child and the Young Saint John (Barcelona, MNAC, 005690-000), created by Joan de Borgonya (doc. 1496-1525). This work displays a remarkable deployment of visual resources and presents scenes linked to Mary, the protagonist of some key episodes in the history of human redemption, and the Childhood of Jesus. So far, no work has been identified containing all the represented elements; however, it is evident that the artist drew inspiration from the work of other masters, as we will detail throughout the text. Through our analysis, we seek to offer a possible interpretation: the Salvation of man through the divine word and conversion.